PENERAPAN SISTEM PEMBELAJARAN DALAM JARINGAN UNTUK MENINGKATKAN KUALITAS BELAJAR DALAM MENGHASILKAN SISWA 4.0 - Heni Sulistiani; Yuri Rahmanto; Ade Dwi Putra; Eko Bagus Fahrizqi; setiawansyah setiawansyah (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2021)
Schools are educational institutions that are formal, non-formal and informal, where their establishment is carried out by the state or private sector with the aim of providing teaching, managing and educating students through guidance provided by educators or teachers. utilizing information technology for learning systems during the Covid-19 pandemic is not yet available, only using Google Classroom at SMK Negeri 7 Bandar Lampung. Not yet optimal knowledge of teachers and students in using information and communication technology in learning systems in the network. The ability of teachers to utilize e-learning-based learning systems is still not optimal. The ability of students to use e-learning-based learning systems is not yet optimal. the learning process before the Covid-19 pandemic still uses conventional methods, namely teachers are still conducting face-to-face learning with students, problems occur when the teacher is unable to attend, the class taught by the teacher will be empty, so students cannot get the desired learning material, this is clearly detrimental to students because the learning material will be explained late by the teacher. training on the use of this application, teachers in using information and communication technology in making learning media more interesting and better, and will facilitate the learning process for students